(3OjhGf GHf cehfgs - (3GdMGL eMeO Ydj Hf eMeO Hf YjSi GdfLaj GdGSOj GdMGFQj, GHf cehfg,J (B1282 (3g` s ((3eMeO GdSeGhj s)
(3ChdgG (B:s
(3bGd QMeg Gddg QGKjkG CHG YHOGddg GdMSjf Ydjg GdSdGe ef bGajI GdgeRI(B: (3eG HGd Yjfj HYO cTa ZWGFgG bPa GdCSi EfSGfgG aj eGFgG s
(3BNQgG (B:s
(3jG GHf Cej ef ojMGej ddYjGd JbWY GdHjOGA eG Hjf GdQLGd gPG BNQ eG GSJWYJ Cf CLeYg ef TYQ gPG GdaMd hjfJgj gPG GdedMb Hbhdg(B: (3ahGYLHG cja GMJQbJ hEffj HdLI JjGQ GdeOGaY CSHM s
(3JGQjN haGI GdeDda aj GdCYdGe (B275(3g```s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B58s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B187 s
Keywords: (3GdCOHs